Intramuscular compared to intravenous midazolam for paediatric sedation: A study on cardiopulmonary safety and effectiveness - Mohammad-Reza Ghane; Hamid-Reza Javadzadeh; Sadrollah Mahmoudi; Bita Najafian; Amin Saburi (Wolters Kluwer Medknow Publications, 2014)
Background: Sedation in children remains a controversial issue in emergency departments (ED). Midazolam, as a benzodiazepine is widely used for procedural sedation among paediatrics. We compared the effectiveness and safety of two forms of midazolam prescription; intramuscular (IM) and intravenous (IV). Patients and Methods: A cohort study was conducted on two matched groups of 30 children referred to our ED between 2010 and 2011. The first group received IM midazolam (0.3 mg/kg) and the second group received IV midazolam (0.15 mg/kg) for sedation. For evaluating effectiveness, sedation, irritation and cooperation score were followed every 15 min for 60 min and for safety assessment, vital signs and O 2 saturation were observed. Results: Mean age was 6.18 ± 2.88 years and 31 patients (51.7%) were male. All patients were sedated completely after using first dose. There was an overall complication rate of 68.3%. 35 (58.3%) patients presented euphoria as the most common complication, but there was no statistical difference between the two groups (P = 0.396). Cases who received IV midazolam became sedated faster than those received IM midazolam (P > 0.001). The vital signs including heart rate, respiratory rate, systolic blood pressure and O 2 saturation changed significantly between and within groups during the sedation (P < 0.05). Conclusion: Both forms of midazolam, IM and IV, are effective and safe for paediatric sedation in ED. Although the sedative with IV form might appear sooner, IM form of midazolam can be effectively used in patient with limited IV access. Patients are better to observe closely for psychological side-effects.